COMBINATION OF PHYSICAL THERAPY AND AUTOGENIC TRAINING IN THE REHABILITATION PROCESS OF PATIENTS SUFFERING FROM RHEUMATOID ARTHRITIS - Drevitska, O. O.; Bulda, V. I.; Khomchenkova N. І. (Rehabilitation and Recreation, 2024)
The aim of this study is to develop and identify the effectiveness of a combination of physical therapy (PT) and autogenic training (AT) classes for patients with rheumatoid arthritis (RA) during the outpatient stage of treatment. Material. Thirty-five women aged between 30 and 40, suffering from RA, were examined. After randomization, 18 patients were assigned to the main group (MG), and 17 patients to the comparison group (CG). The PT program lasted for 10 weeks and included educational talks, joint exercises, aerobic classes, and recommendations for self-massage, running concurrently in both groups. The difference in MG was that patients were taught the principles and process of conducting ST during the first 2 weeks. The following parameters were compared between the groups: age of patients, duration of illness, number of affected joints, activity of the inflammatory process according to the CDAI index; body mass index – BMI (kg/m²); results of the pain study according to VAS; level of fatigue according to the FAS scale; presence and level of depression according to the PHQ-9 test. Results. Prior to the PT program, there were no significant differences between MG and CG patients in terms of age, disease duration, BMI, and activity of the inflammatory process according to CDAI indicators. Additionally, there was no significant difference in the intensity of pain sensations (according to VAS), and indicators of fatigue and depression according to FAS and PHQ-9 tests. Examination of various indicators after PT showed improvements in both groups, specifically: a decrease in the severity of the inflammatory process according to the CDAI index (in MG by 3.5 points, p < 0.05; in CG by 2.7 points, p < 0.05), fatigue (according to FAS): in MG by 4.3 points, p < 0.05; in CG by 3.6 points, p < 0.05), and depression (according to PHQ-9: in MG by 2.7 points, p < 0.05; in CG by 2.3 points, p < 0.05). The sensation of pain after PT in the MG, measured using the Visual Analog Scale (VAS), decreased significantly from 5.2 to 3.8 points (p < 0.05). The decrease in pain sensation after PT in the CG from 5.1 to 4.0 did not reach a 95% probability (p > 0.05). Conclusions. PT is an important factor in the rehabilitation of patients with RA. Post-PT pain sensation (according to VAS) was lower in the MG (p < 0.05), while in the CG, the decrease did not reach a 95% probability (p > 0.05). The PT program implementation in both the MG and CG showed a probable decrease in indicators of the inflammatory process, fatigue, and depression. Therefore, the introduction of AT into the rehabilitation process together with PT may be promising for further research.